USP8 inhibition regulates autophagy flux and controls Salmonella infection - Santelices, John; Ou, Mark; Maegawa, Gustavo H B; Hercik, Kamil; Edelmann, Mariola J (Frontiers in cellular and infection microbiology, 2023)
INTRODUCTION: Ubiquitination is an important protein modification that regulates various essential cellular processes, including the functions of innate immune cells. Deubiquitinases are enzymes responsible for removing ubiquitin modification from substrates, and the regulation of deubiquitinases in macrophages during infection with Salmonella Typhimurium and Yersinia enterocolitica remains unknown. METHODS: To identify deubiquitinases regulated in human macrophages during bacterial infection, an activity-based proteomics screen was conducted. The effects of pharmacological inhibition of the identified deubiquitinase, USP8, were examined, including its impact on bacterial survival within macrophages and its role in autophagy regulation during Salmonella infection. RESULTS: Several deubiquiitnases were differentially regulated in infected macrophages. One of the deubiquitinases identified was USP8, which was downregulated upon Salmonella infection. Inhibition of USP8 was associated with a decrease in bacterial survival within macrophages, and it was found to play a distinct role in regulating autophagy during Salmonella infection. The inhibition of USP8 led to the downregulation of the p62 autophagy adaptor. DISCUSSION: The findings of this study suggest a novel role of USP8 in regulating autophagy flux, which restricts intracellular bacteria, particularly during Salmonella infection.
Keywords: endopeptidasy; Ubiquitination; Ubiquitin Thiolesterase; Endosomal Sorting Complexes Required for Transport; autofagie; Salmonella typhimurium; lidé; Endopeptidases; Autophagy; ubikvitinace; endozomální třídící komplexy pro transport; salmonelóza; Deubiquitinating Enzymes; thiolesterasa ubikvitinu; deubikvitinasy; Salmonella Infections; Humans